(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Language contact, the interaction between speakers of different languages, has long been recognized as a catalyst for linguistic change, particularly in phonological systems. This research paper examines how language contact influences phonological systems through processes such as borrowing, convergence, and diffusion. By synthesizing historical examples, empirical studies, and theoretical frameworks, this study investigates the mechanisms behind phonological changes observed in languages that come into contact. Case studies from diverse linguistic contexts illustrate the varied outcomes of language contact on phonological structure, highlighting both the adaptive nature of languages and the sociocultural implications of linguistic exchange. Through a multidisciplinary approach combining linguistic analysis with sociolinguistic insights, this paper contributes to a deeper understanding of how language contact shapes phonological diversity and evolution in a globalized world.